Pendampingan Edukasi Strategi Pemasaran Pertanian Sayur Mayur dan UMKM Keripik Kentang di Desa Margaluyu - Arya Darmawan; Otti Ilham Khair; Rini Ratnaningsih (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to provide understanding of the importance of attractive branding and marketing, as well as to develop and enhance skills in business management, marketing, and product innovation, which overall can help farmers improve their standard of living. The implementation of this community service activity took place over 2 days, on Friday, March 1, 2024, and Saturday, March 2, 2024, at the Margaluyu Village Hall, Pangalengan, Bandung, West Java. This community service activity has provided significant benefits to the community, especially the participants, by enhancing their understanding of marketing strategies for processed products. This enables them to more effectively promote their products to consumers outside the village. Through training in digital marketing strategies, participants are equipped with valuable understanding and skills in utilizing social media and online marketplace platforms to market their processed products. Thus, this activity not only imparts new knowledge but also provides practical tools that assist participants in increasing visibility and market access for their products, supporting the overall development of their businesses.